Bhārata viplavapandhānu cūpina Telaṅgāṇā sāyudha pōrāṭaṃ - Vēṅkaṭēśvararāvu, Dēvulapalli (Proliṭēriyanlain Pracuraṇalu, 1982)
On the peasant uprisings in the Telangana region of Andhara Pradesh, 1946-1951, and the path of Indian revolution; Marxist viewpoint.